Indexes of nonspecific immune protection of the vagina before and after treatment of bacterial vaginosis - M. M. Rakhmatullaeva (Медицинская иммунология, 2025)
Bacterial vaginosis is a serious public health problem due to the increased risk of sexually transmitted infections and development of various obstetric and gynecological disorders. The local production of cytokines and antimicrobial peptides in the vagina plays an important role in regulation of genital tract immunity. The aim of the present study was to compare microflora and factors of nonspecific protection in vaginal environment in women with bacterial vaginosis before and after treatment. Our study included 110 patients with bacterial vaginosis (main group) and 26 conditionally healthy women with vaginal normocenosis (control group). The Amsel clinical criteria were determined, the vaginal microbiocenosis was studied using a molecular biology method using the Femoflor-16 test system. The contents of IL-6, IL-8, TNFa, IL-10 cytokines and acute phase proteins of C-reactive protein, C3-complement component and lactoferrin in vaginal secretions were studied by ELISA test systems. Methods of variation parametric and nonparametric statistics were used for statistical analysis. Statistically significant differences were taken at a confidence level of p < 0.05. Bacterial vaginosis was found to be accompanied by increased levels of IL-6, IL-8, TNFa and IL-10 (by 5.6, 5.5, 6.8, 4.1 times, respectively), and C-reactive protein by > 10 times, along with decrease in the C3 component of complement, and lactoferrin by 2.2 and 1.4 times, respectively, in the vaginal discharge (p < 0.001). After treatment of vaginosis, the patient groups with initial local dominance of obligate anaerobes (Sneathia spp. / Leptotrichia spp. / Fusobacterium spp., Megasphaera spp. / Veillonella spp. / Dialister spp., Atopobium vaginae and Mycoplasma hominis) exhibited increased levels of IL-6, TNFa and IL-10, along with low content of the C3 component of complement and lactoferrin. Thus, post-treatment preservation of low C3 component and lactoferrin levels may serve as a marker of recurrent bacterial vaginosis.